The Concept of Implementing Restorative Justice in Relation to the Principle of Ultimum Remedium - Ryan Fadli Siregar; Yasmirah Mandasari Saragih; Muhammad Azhali Siregar (International Journal of Law, Crime and Justice, 2024)
Children are the future generation of the nation that must be protected, especially when dealing with the law. The difficult navigation route passed by children who are suspects of criminal acts has depicted sadness in children that can disturb the child's mental state, in order to avoid this possibility, another method has emerged in child criminal acts, namely restorative justice (diversion) which is in accordance with the principle of ultimum remedy in criminal law. This study aims to understand the concept of implementing restorative justice which is associated with the principle of ultimum remedy, where this study works using qualitative methods and is sorted in descriptive, so that concrete solutions can be found regarding the matter being studied. The results of this study found a match between the concept of restorative justice and the principle in criminal law, namely ultimum remedy where criminal witnesses are the last step in handling child criminal acts. However, in its application, several obstacles were found, one of which was due to the different meanings of justice between the parties.